The complete chloroplast genome of Epimedium wushanense T. S. Ying. (Berberidaceae), a traditional Chinese medicinal herb - Liu, Ting (Mitochondrial DNA B Resour, 2020)
Epimedium wushanense is a well-known medicinal plant in Berberidaceae in China. In this study, we sequenced the complete chloroplast (cp) genome of E. wushanense. The results showed that the cp genome of E. wushanense was 157,283 bp in length, which is composed of a large single-copy region (LSC, 88,579 bp) and a small single-copy region (SSC, 17,082 bp) that were separated by a pair of inverted repeat regions (IRa and IRb, 25,811 bp). The chloroplast genome of E. wushanense contains 112 unique genes, of which are 78 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. The overall GC content was 38.78%. The phylogenetic tree analysis showed that E. wushanense was closely related to E. pseudowushanense, E. lishihchenii, and E. sagittatum.